2016
DOI: 10.1136/thoraxjnl-2015-207315
|View full text |Cite
|
Sign up to set email alerts
|

The validity of health-related quality of life questionnaires in bronchiectasis: a systematic review and meta-analysis

Abstract: This review supports most HRQOL questionnaires used in bronchiectasis have good psychometric properties. There was a weak to moderate association between HRQOL and objective outcome measures. This suggests that HRQOL questionnaires assess a unique aspect of health not captured by objective measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
61
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 36 publications
0
61
1
2
Order By: Relevance
“…In addition patient monitoring should include assessment of symptoms and the impact that these have on health status. This may be best achieved using a validated tool, of which there are many, 339 including tools specifically for bronchiectasis such as the QOL-B. 340 Systematic review has demonstrated that these tools may assess components of health status in bronchiectasis not measured using other outcomes.…”
Section: Section 15mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition patient monitoring should include assessment of symptoms and the impact that these have on health status. This may be best achieved using a validated tool, of which there are many, 339 including tools specifically for bronchiectasis such as the QOL-B. 340 Systematic review has demonstrated that these tools may assess components of health status in bronchiectasis not measured using other outcomes.…”
Section: Section 15mentioning
confidence: 99%
“…340 Systematic review has demonstrated that these tools may assess components of health status in bronchiectasis not measured using other outcomes. 339 Routine monitoring of quality of life may not be needed in all cases but should be considered when higher cost interventions are planned. The optimal tool for monitoring treatment effects has however yet to be determined in bronchiectasis.…”
Section: Section 15mentioning
confidence: 99%
“…In adults, the St George’s Respiratory Questionnaire (SGRQ) and the Leicester cough questionnaire have been commonly used to assess QOL in patients with respiratory disease, other than asthma (9). …”
Section: Tools Used To Assess Qolmentioning
confidence: 99%
“…It consists of 50 questions grouped into 3 domains: symptoms, activity, and impact (11). In a recent systematic review of QOL questionnaires in patients with bronchiectasis, there was strong correlation with subjective symptoms but a weak correlation with objective assessments such as FEV 1 , radiological scoring, and exercise capacity (9). The SGRQ has also been used to assess QOL in children with bronchiectasis as young as 8 years old (12).…”
Section: Tools Used To Assess Qolmentioning
confidence: 99%
“…Further, it should be capable of changing to a clinically significant degree (i.e. a degree noticeable to the patient) after the administration of a specific therapy, or after relevant changes in the patient's circumstances [5]. Even the best questionnaire is useless, however, if nobody uses it, so another extremely important prerequisite is simplicity in terms of construction, handling and interpretation.…”
mentioning
confidence: 99%